Vue.js: Creating and Hosting a Full-Stack Site. - Wassell, Shaun (linkedin.com, 2023)
Create and host a full-stack site from scratch. Learn how to set up a front end using Vue.js, set up a back end using Node.js and MongoDB, and take your site live.